[SOUND CONTACTS] Aspects of touch and timbre in piano performance. The effects of key velocity, articulation and temporal duration on sound - Kojucharov, Eleonora (Analitica. Rivista online di studi musicali, 2014)
The concept of touch in piano pedagogy is generally described by using abstract adjectives often linked to imagination, leading to a blurred and controversial definition of the term touch, often confused with timbre. In the last decades, new data-collection technologies and MIDI-based analysis allowed researchers to measure key-control specific features in timbre nuances modeling [Goebl-Bresin-Galembo 2004; Bernays-Traube 2011; 2013]. Within the field of piano performance, the present study attempts to objectively describe piano touch and the means with which it can be controlled, by: (1) providing elements for an adequate scientific understanding of touch; (2) clarifying the relationship between touch and timbre; (3) defining the extent to which the parameters of key-velocity, tempo and articulation vary as a function of different types of touch.